2022
DOI: 10.51253/pafmj.v72i6.4541
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Primigravida with Unengaged Fetal Head at Term or Onset of Labour

Abstract: Objective: To investigate the duration and course of labour, the need for intervention and feto-maternal outcome in a primigravida with an unengaged fetal head at term in labour. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jun 2018 to Oct 2019. Methodology: This study was carried out on 150 term primigravida women with an unengaged head in labour. Informed consent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…14,18 Caesarean rate in our study in unengaged was 63.1% & it was a bit high when compared to some studies. A study carried out by Haroon M et al in unengaged women found that the cesarean delivery rate was 33.34% 19 . Similar findings were observed in a study conducted in Services Hospital Lahore in Primigravida with an unengaged head at term and they found an incidence of 38% for cesarean delivery.…”
Section: Discussionmentioning
confidence: 98%
“…14,18 Caesarean rate in our study in unengaged was 63.1% & it was a bit high when compared to some studies. A study carried out by Haroon M et al in unengaged women found that the cesarean delivery rate was 33.34% 19 . Similar findings were observed in a study conducted in Services Hospital Lahore in Primigravida with an unengaged head at term and they found an incidence of 38% for cesarean delivery.…”
Section: Discussionmentioning
confidence: 98%